LncRNA-ENST00000421645 Upregulates Kank1 to Inhibit IFN-γ Expression and Promote T Cell Apoptosis in Neurosyphilis - Wu, Kai-Xuan; Wang, Xiao-Tong; Hu, Xin-Lin; Jiang, Xiao-Yong; Zhuang, Jing-Cong; Xu, Yan-Zhu; Lin, Li-Rong; Tong, Man-Li; Yang, Tian-Ci; Liu, Li-Li (Frontiers in Microbiology, 2021)
Long non-coding RNAs are involved in many infectious diseases. Our previous studies showed that lncRNA-ENST00000421645 expression is increased in T lymphocytes of neurosyphilis patients compared to healthy controls. However, whether lncRNA-ENST00000421645 has biological functions remains unclear. The current study was undertaken to understand the mechanism of lncRNA-ENST00000421645 in T lymphocyte function in neurosyphilis patients. The lncRNA-ENST00000421645 pull-down assay showed that lncRNA-ENST00000421645 acted on the acetylase NAT10. The chromatin immunoprecipitation (ChIP)-PCR results showed that lncRNA-ENST00000421645 promoted the acetylation of histone H3K27 adjacent to the Kank1 promoter, thereby promoting Kank1 protein expression. Kank1 promotes 14-3-3 protein expression, inhibits NF-kB activation, inhibits IFN-γ secretion by T lymphocytes, and promotes T lymphocyte apoptosis. Taken together, our findings suggest a novel mechanism that LncRNA-ENST00000421645 upregulates Kank1 to inhibit IFN-γ expression and promote T cell apoptosis in neurosyphilis.